Clostridioides difficile ribotypes 001 and 126 were predominant in Tehran healthcare settings from 2004 to 2018: a 14-year-long cross-sectional study. Issue 1 (1st January 2020) - Azimirad, Masoumeh; Krutova, Marcela; Yadegar, Abbas; Shahrokh, Shabnam; Olfatifar, Meysam; Aghdaei, Hamid Asadzadeh; Fawley, Warren N.; Wilcox, Mark H.; Zali, Mohammad Reza
ABSTRACT: Clostridioides difficile infection (CDI) remains a major healthcare problem worldwide, however, little is known about CDI epidemiology in Iran. Between December 2004 and November 2018, 3649 stool samples were collected from patients in 69 hospitals and medical centres in Tehran and were cultured for the presence of C. difficile ; isolates were characterized by PCR ribotyping and toxin genes detection. A total of 582 C. difficile isolates were obtained and the overall CDI prevalence was 15.9%; 290 (49.8%) cases were healthcare-associated (HA) and 292 (50.2%) cases were community-associated (CA). Of these, DNA of 513 isolates submitted for ribotyping. The ribotype and/or WEBRIBO type could be assessed in 366 (62.9%) isolates. The most frequent RTs were 001 ( n = 75, 12.9%), 126 ( n = 65, 11.2%) and 084 ( n = 19, 3.3%); the toxin gene profile tcdA + B + /cdtA + B + ( n = 112, 19.2%) was the most common. Fifteen C. difficile isolates (2.6%) did not carry any toxin genes. There was no difference between frequently found RTs in HA-CDI and CA-CDI, except for RT 029 which was more likely to be associated with healthcare origin (12/15, p -value = 0.02). No isolate of RTs 027 or 078 was identified. Importantly, RTs 031, 038, 039, 084, 085 reported previously as RTs with an absence of toxin genes, revealed the presence of toxin genes in our study. Using Simpson's reciprocal index of diversity, we found that RT diversity decreased as the prevalence of the RT 084 increased ( R = −0.78, p -value = 0.041). Different patterns in CDI epidemiology underscore the importance of local surveillance and infection control measures in Tehran healthcare settings.